Listening through the Works of Duchamp: : a kaleidoscope of Cagean sounds - Alfradique Leite, Carolina (Revista Brasileira de Estudos da Presença, 2025)
This article explores the relationship between the works of John Cage and Marcel Duchamp, setting the scene both as a place of transition from the visual to the sonic and as a favorable space for the contemporary reinterpretation of artistic modernity. In this sense, we discuss how Cage takes the unintentional sounds generated by the manipulation and displacement of the French artist’s works as a starting point for his own artistic works. The relationship between the contemporary and the modern is therefore revisited through the prism of dissent regarding their periodization, questioning the merely diachronic opposition.